2010
DOI: 10.1590/s1519-566x2010000200004
|View full text |Cite
|
Sign up to set email alerts
|

Species richness in natural and disturbed habitats: Asteraceae and Flower-head insects (Tephritidae: Diptera)

Abstract: -Anthropogenic changes in the landscape result in an environmental mosaic with serious consequences for biodiversity. The aim of the present study was to assess the effects of the anthropogenic changes on Asteraceae richness and abundance, and to evaluate the consequences for the richness of Tephritidae assemblages in fi ve sampling sites, with three sampled habitats in each: cerrado (Brazilian savanna), eucalyptus stands and pasture. Sampling was carried out in 15 random transects (cerrados and one pasture) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 33 publications
(22 reference statements)
0
14
0
4
Order By: Relevance
“…Plant assemblages in Eucalyptus stands were subsets of cerrado sites. Otherwise, pasture assemblages included 12 species that were exclusive to them and these assemblages were only partially subsets of cerrado sites (see also Diniz et al . 2010).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Plant assemblages in Eucalyptus stands were subsets of cerrado sites. Otherwise, pasture assemblages included 12 species that were exclusive to them and these assemblages were only partially subsets of cerrado sites (see also Diniz et al . 2010).…”
Section: Resultsmentioning
confidence: 99%
“…2009). Therefore, pasture management may well contribute to reducing isolation effects on insect populations in the cerrado (Diniz et al . 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…But, it remains uncertain how the insect communities of the Cerrado respond to the strong heterogeneity of the biome, as well as to the increasing levels of anthropogenic disturbance. Previous studies have indicated that the effects of seasonality (Morais et al ., ; Pinheiro et al ., ; Scherrer et al ., ; Silva et al ., ), vegetation diversity (Diniz et al ., ; Morais et al ., ), and vegetation heterogeneity (Pacheco & Vasconcelos, ), as well as those of fire (Vasconcelos et al ., ; Louzada et al ., ; Diniz et al ., ), fragmentation (Brandão et al ., ), afforestation (Gries et al ., ), and the introduction of exotic grasses (Almeida et al ., ; Almeida‐Neto et al ., ), can be reflected by insect communities in the Cerrado. But, this emerging body of knowledge is focused on the most studied insect taxa, such as butterflies, ants and beetles.…”
Section: Introductionmentioning
confidence: 98%
“…Existe pouca informação sobre biologia e taxonomia de grande número de espécies de tefritídeos associados à Asteraceae (FOOTE et al, 1993). No Brasil, os principais estudos realizados sobre a interação entre tefritídeos e Asteraceae são os realizados por: Lewinsohn (1991); Prado et al (2002); Prado e Lewinsohn (2004); Almeida et al (2006), Diniz et al (2010), Fávero et al (2010) havendo pouquíssimas informações até o momento sobre tal assunto em Santa Catarina.…”
Section: Introductionunclassified